AN ANATOLIAN CHIEF-GOVERNOR IN ESAD ADIL'S WRITINGS: ILYAS PASHA - İhsan SATIŞ (Fırat University, 2019)
Esad Adil has published Irmak Journal which included many topics such as poem, prose, folk-literature and history while he was studying at the Faculty of Law in Ankara University. In this journal, Esad Adil wrote eight articles about Ilyas Pasha who lived in seventeenth-century. Ilyas Pasha was the son of an archer from Balıkesir. He worked his way up from a cavalryman to the governor of a sanjak and he became the Governor of Rumeli in 1621. He joined the Baghdad campaign as the chief-governor of Anatolia in 1625 and carried out important tasks on this campaign. Although he was of great service during the campaign, he rebelled when he was commissioned to terminate the banditry activities in Anatolia. IV. Murad did not confront Ilyas Pasha right after he had gathered plenty of partisans. Sending away him from his influence area, he had been given chief-governorship of Damascus Province to separate him from his partisans. However, after being aware of the case, Ilyas Pasha gave up going to Damascus and send there Yusuf Agha as proxy. Thereupon, Sultan ordered Ilyas Pasha to be catched. Vizier Gurcu Ahmed Pasha and Kucuk Ahmed Pasha The Chief-Governor of Anatolia had been taken charge for this duty. Ilyas Pasha was at bay after Alasehir War and was withdrowed to Castle of Bergama. When Kucuk Ahmed Pasha promised to provide him to be forgiven, he surrendered. When Ilyas Pasha surrendered, his partisans’ lands had been taken back and Pasha had brought to Istanbul. Than, Ilyas Pasha was executed by head cut off. On this paper, life and the period of Ilyas Pasha are investigated based on writings about him written by Esad Adil.